Developing â€œLeadership Intelligence (CI2) Frameworkâ€ Inside Social Media to Develop An Ethical Leader using the Johari Window Method - Gamayanto, Indra; Christian, Henry; Wibowo, Sasono; Setiadi, De Rosal Ignatius Moses; Purnamasari, Devi; sukamto, Titien S (Program Studi Sistem Informasi Universitas Atma Jaya Yogyakarta, 2019)
At this time, leadership and social media are two things that cannot be separated. Social media becomes an information technology media for leaders to be able to communicate about their vision and purpose. Therefore, leaders must be able to use social media effectively in order to influence the community with what they think. There are three problems caused by leaders in social media which are classified into three types such as narcissistic, compulsive and paranoid. These three things become big problems in leadership on social media and therefore, we need the formula to solve the problems. The Johari Window method is a method that has four perspectives in developing four leadership classifications such as open leaders, blind leaders, hidden leadership, and unknown leaders. If these three types and four classifications are put together, a framework will be produced called